Investigating salinity variation in estuarine system: effects of upstream water levels – a laboratory study - Nur Aqilah Nabihah Mahamood,; Nuryazmeen Farhan Haron,; Siti Nurhayati Mohd Ali,; Mohammad Naser Sediqi,; Mazlin Jumain, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Estuaries, where freshwater rivers converge with saline ocean water, play vital roles in supporting marine life and human civilization. This study examines salinity dynamics in estuarine systems, focusing on the impact of upstream water level changes on saltwater intrusion. Through experimental manipulation in an idealised channel, varying water depths upstream were simulated. With a 15cm and 30cm differential in the water level upstream, freshwater flows from one end of the flume overflowing a moveable weir at the other end. The saline water combined with a red-coloured tracer to differentiate saltwater from freshwater, where the movement and distribution of saltwater may be roughly observed throughout the experiment and pulled upstream by the force of gravity. The analysis of the investigation was done spatially and temporally in order to determine the salinity mixing in the longitudinal, horizontal, and vertical at different heights of upstream water level. Analysis revealed that higher upstream water levels led to decreased salinity levels due to increased freshwater flow. The water level was influenced and affected the time taken for salinity to reach an equilibrium state. Hence, the higher the water level of upstream, the lower the salinity level. Findings underscore the importance of understanding how estuarine salinity is influenced by upstream conditions for effective management and conservation efforts